International portfolio diversification in the Nigerian stock market: A global financial crisis perspective - Olufemi Adewale Aluko; Oladapo Fapetu; Bolanle Aminat Azeez (Future Business Journal, 2018)
This study examines the feasibility of international portfolio diversification in the Nigerian stock market. It investigates the relationship between the Nigerian stock market and 5 developed stock markets (US, UK, Japan, Germany and France) in the context of the global financial crisis. The Vector Autoregressive (VAR) Granger causality test results show that the Nigerian stock market and all the developed stock markets are not linked in all the sub-sample periods except the Japanese stock market in the post-crisis period, thus implying that international portfolio diversification is possible in the Nigerian stock markets except Japanese investors in the post-crisis period. Under the full sample period, only the Japanese and German stock markets are not linked to the Nigerian stock market and this indicates international portfolio diversification is feasible for only Japanese and German investors in Nigeria. The Generalized Method of Moments (GMM) regression results indicate that only German and French stock markets have significant impact on the Nigerian stock market in the pre-crisis period, but none of the developed stock markets exert significant impact in the crisis period. In the post-crisis period, only the German stock market is significantly related to the Nigerian stock market. The regression estimates reveal that only the Japanese, German and French stock markets are significantly related to the Nigerian stock market over the full sample period.
Keywords: G11; G15; 650; Developed stock markets; Global financial crisis; International portfolio diversification; Nigerian stock market